Trio Texture in Choral Arrangements and Polyclavier Organ of Southern Germany in the First Third of the 16th Century - Fedosia W. Tabyisova (Современные проблемы музыкознания)
The article is an attempt to establish a relationship between the structure of large South German church organs of the first third of the 16th century and the compositional features of the thencontemporary organ works. The historical boundaries of the Renaissance in German architecture and music do not coincide, while an organ may be viewed as an architectural element. This contradiction presents a certain difficulty. In the indicated period, the late Gothic architectural style, which preceded the Renaissance, played a leading role. As we see it, the organ music of this time, usually attributed to the Renaissance, reflected the transition from the late Gothic to the Renaissance. This complex repertoire is marked by the coexistence and interaction of three general trends. Among them are archaic polymelodic polyphony as well as new techniques: the method of coloring that spread in Southern Germany and imitation borrowed from the European North. A polyclavier organ, which we take as the standard of the South German instrument, is called a late Gothic spaltsatz organ (spätgotische Spaltsatz-Orgel) in German musicology. The trio texture found in choral arrangements, in our opinion, most fully and accurately reflects the polyclavier structure and timbre richness of the large church organs of South Germany.